Effect of Punica granatum on dexamethasone induced immunosupression in rabbits - ROSS, R GRACIOUS; SELVASUBRAMANJAN, S; SAMUEL, J JEYASEKARAN (The Indian Journal of Animal Sciences, 2014)
The effect of Punica granatum fruit rind (PGFR) powder on the immune system suppressed in dexlimethasone treated rabbits was evaluated. Rabbits were treated with dexamethasone @ 2 mg/kg s.c. for 7 days alone in 1 group and along with POFR powder @100 mg/kg p.o. for 10 days in another group with a third group as control tG study the humoral immune response. Similarly another 3 respective groups were used for studying call mediated immune response (CMIR). There was significant variation in the humoral immune response between groups as evidenced by antibody titre, serum albumin globulin ratio and also in CMIR as shown by leuoocyte migration inhihition, delayed hypersensitivity and total and differential leucocyte count. PGFR powder was able to restore the immune system suppressed by-dexamethasone in rabbits.